RISK FACTORS FOR LEPROSY: A SYSTEMATIC REVIEW - Pertiwi, Aisyah Noer Auliyah Madani; Syahrul, Fariani (Universitas Airlangga, 2024)
Introduction: In 2021, the global prevalence rate of registered leprosy cases stands was 16.9 cases per one million people, with a case detection rate of 17.83 new cases per one million people. This indicates a 10.2% rise in new cases compared to the previous year. Aims: This study aims to examine the risk factors associated with leprosy. Methods: The inclusion criteria for this study were articles published in the last five years, available in full-text, and written either in Indonesian or English. Articles that were literature reviews, systematic reviews, meta-analyses, or classified as grey literature were excluded. The exclusion criteria were established to determine which studies to include in this study. Results: This study found that leprosy is associated with household density, personal hygiene, history of contacts, ventilation, humidity levels, BCG vaccination history, flooring type, house lighting, temperature, and wall type. Personal hygiene was identified as the primary risk factor for leprosy based on individual characteristics and behaviors, while household density was identified as the most significant risk factor based on the physical environment of the occupants. Therefore, poor personal hygiene and high residential density increase the risk of leprosy. Conclusion: The key risk factors for leprosy include household density and personal hygiene, while a history of BCG vaccination serves as a protective factor. This study provides valuable information for governments and stakeholders to assess healthy household indicators and promote clean and healthy living practices in communities